Martin Luther King: the peaceful warrior. - Clayton, Ed; Hodges, David (Englewood Cliffs, N.J., Prentice-Hall, 1968)
A biography of the black leader, Martin Luther King, who, encouraged by the teachings of Mahatma Gandhi, inspired the Nation to begin a non-violent campaign for equality.
Bibliography: p. 93.
Keywords: King, Martin Luther; King, Martin Luther